Pengaruh Celebrity Endorser Ruben Onsu dan Brand Awareness Ben's Market terhadap Keputusan Pembelian Konsumen - Sudrajat, Ratih Hasanah; Zahrani, Amelia Devi (Jurnal Common, 2024)
This study aims to investigate the influence of Celebrity Endorser Ruben Onsu and Brand Awareness Ben’s Market on Consumer Purchase Decisions. The research adopts a quantitative approach with a sample of 400 respondents familiar with the online store Ben’s Market. Data were collected through an online questionnaire. Data analysis employed regression analysis to examine the relationship between Celebrity Endorser and Brand Awareness with Consumer Purchase Decisions. The findings indicate that both independent variables significantly contribute to Consumer Purchase Decisions. This study suggests that leveraging Celebrity Endorsers and enhancing Brand Awareness can be effective strategies in influencing consumer purchasing preferences. The research recommends more targeted marketing strategies to strengthen brand awareness and select appropriate endorsers to enhance consumer trust and influence purchasing decisions. . Keywords: Celebrity Endorser; Brand Awareness; Buying Decision.